Integrating ER and Mitochondrial Proteostasis in the Healthy and Diseased Heart - Arrieta, Adrian; Blackwood, Erik A.; Stauffer, Winston T.; Glembotski, Christopher C. (Frontiers in Cardiovascular Medicine, 2020)
The integrity of the proteome in cardiac myocytes is critical for robust heart function. Proteome integrity in all cells is managed by protein homeostasis or proteostasis, which encompasses processes that maintain the balance of protein synthesis, folding and degradation in ways that allow cells to adapt to conditions that present a potential challenge to viability1 (Fig. 1A). While there are processes in various cellular locations in cardiac myocytes that contribute to proteostasis, those in the cytosol, mitochondria and endoplasmic reticulum (ER) have dominant roles in maintaining cardiac contractile function. Cytosolic proteostasis has been reviewed elsewhere2, 3; accordingly, this review focuses on proteostasis in the ER and mitochondria, and how they might influence each other and, thus, impact heart function in the settings of cardiac physiology and disease.